Kebakaran Hutan dan Lahan Gambut: Kajian Teologi Ekofeminisme - Tanda Pinem (Faculty of Theology Duta Wacana Christian University, 2016)
Abstract Smog disaster in Sumatera and Kalimantan Island that came from forest and land burnings showed many interconnected factors. Governmental ideologies factor in development era (e.g. modernization, industrialization, and capitalization in order to increase economics development), lands problems as an impact of development ideologies, corruption, and prestige culture in society (e.g. consumerism, wealthy, succedness, and honor greediness) had participation in this disaster. From the perspective of ecofeminism, this ecological crisis came from an ideology named anthroposentrism, which also an androsentrism. Human interests that became priority in industrial society, especially men who held economics and politics power, was the cause of these ecological damages. The nature of patriarchal system is domination and exploitation who derived from hierarchal dualistic ideology become sources of ecological damage. In this context, economic development factor and life progress became main concern. Finally nature being grinded and became tools to achieve human interests (anthroposentrism). However, in this context women felt chaos very deeply. Women worked to produce family needs with nature. The damage of nature made women work harder. By seeing these conditions, we were invited by ecofeminism to do radical awareness transformation. This transformation was based on the understanding of our local wisdom. Abstrak Bencana kabut asap yang terjadi di Sumatera dan Kalimantan sebagai akibat kebakaran hutan dan lahan, khususnya hutan dan lahan gambut memperlihatkan kesaling-terkaitan berbagai faktor. Faktor ideologi pemerintah dalam menjalankan pembangunan (modernisasi, industrialisasi, dan kapitalisasi demi mengejar pertumbuhan ekonomi), persoalan pertanahan sebagai dampak ideologi pembangunan, korupsi, dan budaya prestise masyarakat (konsumerisme, kekayaan, keberhasilan, dan kehormatan) turut berperan dalam bencana kabut asap ini. Kaum ekofeminisme mengasalkan krisis ekologi ini pada suatu antroposentrisme, yang adalah juga androsentrisme. Prioritas kepentingan manusia dalam masyarakat industri, khususnya kaum laki-laki yang memegang kekuasan ekonomi dan politik menjadi sebab kerusakan ekologis ini. Sifat dan sistem patriarkat, yaitu dominasi dan eksploitasi yang bersumber pada pemahaman dualistik hierarkis merupakan sumber-sumber kerusakan ekologis. Faktor pertumbuhan ekonomi dan kemajuan hidup dijadikan capaian utama. Akhirnya alam ditindas dan dijadikan alat untuk mencapai kepentingan manusia (antroposentrisme). Namun demikian, perempuanlah yang mengalami keterserabutan lebih mendalam. Perempuan bekerja sama dengan alam untuk memproduksi kebutuhan keluarganya. Dengan rusaknya alam membuat perempuan semakin sulit bekerja sama dengan alam. Dengan melihat keadaan ini, kita hendaknya ikut dalam undangan ekofeminisme untuk melakukan transformasi kesadaran radikal. Transformasi ini dilakukan berdasarkan pemahaman kearifan lokal kita.